Implementasi Hukum dalam Memberikan Sanksi terhadap Pembuangan Sampah Sembarangan di Jalan untuk Kelestarian Lingkungan Hidup dengan Menggunakan Teori Hukum yang Hidup (Living Law) : Penelitian - Nainggolan, Dumaria; Agusmidah, Agusmidah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The waste problem is an increasingly complex environmental issue as human activities and needs increase. Although there is a legal basis governing waste management, such as Law Number 18 of 2008 and Medan City Regional Regulation Number 6 of 2015, its implementation remains ineffective. This is evidenced by the continued prevalence of violations such as indiscriminate waste disposal, which causes environmental pollution, declining public health, and ecosystem damage. This study uses a normative juridical method to analyze the application of the law, the effectiveness of sanctions, and obstacles to enforcing regulations related to waste disposal in Medan City. Based on the study, low public awareness, weak supervision, and inconsistency in law enforcement are the main factors hindering the success of waste management. Preventive and repressive efforts need to be strengthened through education, firm supervision, and the implementation of effective sanctions in accordance with the concept of Living Law. Thus, collaboration between the government and the community is key to realizing a clean, healthy, and sustainable environment.